Informal institutions and adaptation: patterns and pathways of influence in a remote Arctic community. Issue 9 (2nd September 2021) - Curry, Tracie; Meek, Chanda; Berman, Matthew
ABSTRACT: Institutions are influential in mediating the impact of adaptation initiatives at the local level, yet there are disconnects between the goals of multi-scale planning initiatives and community priorities. Research to address this challenge primarily focuses on reform to formal institutions in environmental governance. Meanwhile, knowledge of the specific role informal institutions play in governance processes remains limited. This study increases understanding of the interactions between informal institutions and adaptation using a case study of the Native Village of Wainwright on Alaska's North Slope. Qualitative contextual analysis was employed to identify patterns of informal institution and adaptation associations in historic and contemporary situations in Wainwright. The Adaptation Institutional Analysis Framework developed in this paper extends Elinor Ostrom's Institutional Analysis and Development Framework and is used as a tool to analyse and describe these dynamics. Four primary findings resulted from this analysis (1) identification of informal institutions that have a bearing on adaptation to environmental change and adaptive capacity in Wainwright, (2) insight into how the identified institutions relate to each other and to different aspects of local adaptation, (3) identification of changes in informal institutions that have occurred over time and the potential implications of these changes for local adaptive capacity, and (4) potential opportunities to leverage knowledge of informal institution and adaptation relationships in targeted formal initiatives. The outcomes of this study contribute to an improved understanding of the function and potential of informal institutions in adaptation processes, the benefits of which extend beyond the local context of Wainwright.